Penultimate perspectives on the root causes of environmental destruction in Africa - Conradie, Ernst M. (Scriptura, 2017)
In Christian ecotheology in the African context the root causes of environmental destruction in Africa are rightly associated with imperialism and colonialism. In this contribution such root causes are investigated in more detail with reference to Christian discourse on sin. The argument proceeds in three steps. Firstly, some background is offered on root cause analysis as a tool for social analysis. Secondly, the root causes of global environmental destruction are traced backwards to the role of worldviews (‘modernity’) and religious constructions of ultimate reality with reference to the critique against Christianity by Lynn White and others. Thirdly, this analysis is then related to the form of social diagnostics found in Christian discourse on sin. How is the underlying problem perceived? This question is addressed with reference to five classic notions of sin each with a modern correlate found in environmental discourse, namely moral shortcomings (prompting alleged needs for education, economic growth and development), pride (anthropocentrism), greed (consumerism), violence (domination in the name of differences of species), and the privation of the good (alienation from the earth). The last of these resonate well with traditional African notions of land. It also suggests the possibility of ultimate perspective on such root causes of environmental destruction within a Christian context, namely in terms of a broken relationship with the triune God.